UJI ORGANOLEPTIK PADA ES KRIM DADIH SEBAGAI INOVASI MAKANAN SELINGAN SEHAT UNTUK BALITA - Rifdi, Febriniwati; Medhyna, Vedjia; Kesuma, Diajeng (Universitas Fort de Kock Bukittinggi, 2023)
Based on data from the Indonesian Nutrition Status Study (SSGI) in 2021, it was found that the prevalence rate of nutritional status of underweight toddlers had increased from 16.3% to 17%. One of the direct causes of influencing factors is nutritional intake. Curd is a fermented processed product or traditional yogurt typical of Minangkabau West Sumatra that contains probiotics, is highly nutritious, easy to digest, so that it has an impact on increasing the body weight of toddlers. The purpose of the study was to conduct organoleptic tests on curd-based ice cream as a healthy snack innovation. Research type Experiment. The sample in the study were 20 toddlers aged 2-5 years and 20 mothers of toddlers, taken using purposive sampling technique. Data analysis includes univariate analysis with organoleptic tests. The results showed that organoleptic tests found that 55% of respondents really like curd-based ice cream, 50% like the color of ice cream, 60% really like the aroma of ice cream, 55% like the soft texture of ice cream, 55% stated a sweet taste in curd-based ice cream. The conclusion in this study is that toddlers like curd-based ice cream and can help meet daily nutritional needs in toddlers aged 2-5 years. It is hoped that all parties, especially those who have toddlers, will take advantage of curd processing innovations so that highly nutritious traditional foods can be recognized and consumed by children so that they can preserve traditional foods while being useful in improving nutritional status in toddlers.Keywords : Curd, Toddlers, Weight, Organoleptic